Environmental disclosure quality: Examining the impact of the stock exchange of Malaysia's listing requirements - Norhayati, Abdullah; A. H., Fatima; Maliah, Sulaiman (Emerald Group Holdings Ltd., 2015)
Purpose – The purpose of this study is to investigate the environmental disclosure (ED) quality of public-listed companies (PLCs) in environmentally sensitive industries (ESI) in Malaysia in 2005 and 2009 (two years before and two years after the mandatory corporate social responsibility (CSR) requirement of Bursa Malaysia (BM)). BM (The Stock Exchange of Malaysia) has made CSR, including ED in annual reports mandatory since 2007. This study compares environmental reporting (ER) before and after the 2007 mandatory reporting requirement to determine if this command and control mechanism has had any effect on the quality of ED.